Analysis of the Needs for Developing Innovative Chemistry Teaching Modules Based on Integrated Problem Based Learning with Local wisdom - Tini Sulastri; Nurfajriani Nurfajriani; Ramlan Silaban (Proceeding of the International Conference on Mathematical Sciences, Natural Sciences, and Computing, 2024)
This study aims to analyze the quality of Grade XI SMA/MA chemistry textbooks, aligning with the standards set by the National Standards Agency for Education (BSNP). This research employs the Research and Development (R&D) method, specifically the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation), with both qualitative and quantitative approaches. The results indicate that the textbooks scored: 3.37 for content validity, 3.87 for language, 3.85 for presentation, and 3.69 for graphics, categorizing them as highly valid.